2017
DOI: 10.1002/berj.3291
|View full text |Cite
|
Sign up to set email alerts
|

The development and validation of a scale measuring teacher autonomous behaviour

Abstract: In the current study a multi-dimensional scale that measures teacher autonomous behaviour is presented. The scale is applicable across the following educational sectors: primary education, secondary education, and vocational education. Based on an elaborate literature study, four theoretically relevant dimensions of teacher autonomous behaviour were derived. Psychometric characteristics of the instrument 2 were tested among a sample of Dutch teachers working in primary, secondary, and vocational education (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 46 publications
1
27
0
3
Order By: Relevance
“…It is a sense of independence to make professional decisions related to their job (Benson, 2016). The researchers demonstrated that professionalism and empowerment were shown to increase as curricular autonomy increased, which could mean that autonomy would be one encouraging structural factor for empowerment (Evers et al, 2017). As stated by Berry et al (2010), teachers that are provided autonomy and independence tend to become more good teachers; this is verified by the findings of the CTQ's survey of a big urban area in North Carolina; these findings suggested empowerment as a crucial facet in increasing student success.…”
Section: (V) Autonomymentioning
confidence: 82%
“…It is a sense of independence to make professional decisions related to their job (Benson, 2016). The researchers demonstrated that professionalism and empowerment were shown to increase as curricular autonomy increased, which could mean that autonomy would be one encouraging structural factor for empowerment (Evers et al, 2017). As stated by Berry et al (2010), teachers that are provided autonomy and independence tend to become more good teachers; this is verified by the findings of the CTQ's survey of a big urban area in North Carolina; these findings suggested empowerment as a crucial facet in increasing student success.…”
Section: (V) Autonomymentioning
confidence: 82%
“…TABS was developed by Evers, Verboon and Klaeijsen (2017), and consists of 20 items, measured on a seven-point Likert scale from (1= almost never) to (7= almost always). It measures four dimensions of teacher autonomous behavior: primary work processes in the class(6 items, Cronbach alpha= 0.87), curriculum implementation (6 items, Cronbach alpha= 0.89), participation in decision making at school (4 items, Cronbach alpha= 0.82), and professional development (4 items, Cronbach alpha= 0.94).…”
Section: Teacher Autonomy Behavior Scale (Tabs)mentioning
confidence: 99%
“…The CKP questionnaire was designed to evaluate self-assessed competence development during courses that use group work or collaborative assignments as instructional approaches. Empirically, this article examines construct validity in the questionnaire (see Evers, Verboon, & Klaeijsen, 2017;Jones & Paulhus, 2014;Marsh et al, 2009). Based on a dataset from HE courses, the research questions addressed were:…”
Section: In Digital Environmentmentioning
confidence: 99%